The Interests of Women A look into the Abortion Case-law of the European Court of Human Rights - Suihkonen, Matilda (fi=Turun yliopisto|en=University of Turku|, 2017)
This master´s thesis is focused on the abortion case-law of the European Court of Human Rights. The thesis discusses the following research questions: How has the abortion case-law of the ECTHR evolved? How have the women´s interest arguments influenced the case-law? The questions are answered with the help of the abortion related cases of the European Court of Human Rights from the HUDOC-database. These are the main sources of this thesis. The aim of this thesis is to reveal, if there are problems related to gender equality in case of abortion. The thesis is directed towards a legal audience. Legal-dogmatic with a feminist point of view is the guiding method of this thesis. The feminist view point focuses on feminist international law. The history of abortion cases in the European Court of Human Rights spans from the 1960s to the present day. The cases mainly concern Article 8 and Article 2 of the European Convention on Human Rights. First the cases were mostly deemed inadmissible. Judgements based on merits begin to appear from the 1990s forward. The defining features of abortion cases are the role of margin of appreciation, role of consensus and the question of the beginning of life. These were used to confirm that there is no specific right to abortion under Article 8. Positive obligation -cases are slightly different from the others. The European Court of Human Rights has granted more protection for women and their right to choose abortion under positive obligations of Member States. The main interests of women discussed in the cases were related to health. These were quite strong arguments and provided protection for the right to choose abortion. Weaker was the interest of personal autonomy. Other interests, such as the general status of women, were not important. It seems that the European Court of Human Rights has been first reluctant to hear abortion cases and then reluctant to grant an explicit right. Moral objections from Member States have resulted in the European Court of Human Rights taking a subsidiary role in the abortion discussion. The turn to positive obligations has however, been a mediating tool to enhance the rights of women, without creating a right to access to abortion.